2008
DOI: 10.1002/pmic.200700955
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the neuroprotective mechanisms of acupuncture treatment in a Parkinson's disease mouse model

Abstract: Acupuncture is frequently used as an alternative therapy for Parkinson's disease (PD), and it attenuates dopaminergic (DA) neurodegeneration in the substantia nigra (SN) in PD animal models. Using proteomic analysis, we investigated whether acupuncture alters protein expression in the SN to favor attenuation of neuronal degeneration. In C57BL/6 mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP, 30 mg/kg/day), intraperitoneal (i.p.) for 5 days, 2 or 100 Hz electroacupuncture (EA) was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…Acupuncture therapy has also been implicated in increasing various neuroprotective agents (such as brain-derived neurotrophic factor, glial cell linederived neurotrophic factor and cyclophilin A) and attenuating oxidative stress in a neurodegenerative disease animal model. [49][50][51][52][53] Based on the above research, we hypothesise that the mechanism of acupuncture in increasing the number of neurons might be regulated by the interaction of three factors, as follows: (1) more neurons are generated during acupuncture; (2) cell death is decreased; or (3) the expression of various neuroprotective agents is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture therapy has also been implicated in increasing various neuroprotective agents (such as brain-derived neurotrophic factor, glial cell linederived neurotrophic factor and cyclophilin A) and attenuating oxidative stress in a neurodegenerative disease animal model. [49][50][51][52][53] Based on the above research, we hypothesise that the mechanism of acupuncture in increasing the number of neurons might be regulated by the interaction of three factors, as follows: (1) more neurons are generated during acupuncture; (2) cell death is decreased; or (3) the expression of various neuroprotective agents is increased.…”
Section: Discussionmentioning
confidence: 99%
“…EA treatment was performed twice a week with 14-week (98-day)-old male hSOD1 G93A transgenic mice (hSOD1 G93A ) at the Zusanli (ST36) acupoint, which is known to mediate anti-inflammatory effects [21,22] . The location of ST36 was determined according to the human acupoint landmark and a mouse anatomical reference [23,24] . Both control and EA-treated mice were placed under gaseous anesthesia (a mixture of oxygen and nitrous oxide provided at 3% for induction and 1.5% for maintenance) to minimize stress.…”
Section: Methodsmentioning
confidence: 99%
“…36 It has been shown that EA is effective in halting the degeneration of dopaminergic neurons in substantia nigra with individual studies, however the role of HSP had not been studied. 38 Further, in familial amyotrophic lateral sclerosis (FALS) mutant superoxide dismutase 1 (SOD1) aggregates to form intracellular inclusions. Remarkably, primary spinal cord cultures of FALS fails to upregulate HSP70 in response to heat shock, whereas cerebellar, cortical and pyramidal neurons, as well as astrocytes, efficiently upregulate HSP70 in response to heat shock.…”
Section: Acupuncture and Heat Shock Proteinsmentioning
confidence: 99%